Resposta :
Resposta:
[tex]a)\\ 3x^2+5x+2+3x-4=\\ \\ 3x^2+5x+3x+2-4=\\ \\ \boxed{3x^2+8x-2}[/tex]
b)
[tex]3x^2+5x+2-(3x-4)=\\ \\ 3x^2+5x+2-3x+4=\\ \\ 3x^2+5x-3x+2+4=\\ \\\boxed{ 3x^2+2x+6}[/tex]
c)
[tex](3x^2+5x+2)\times(3x-4)=\\ \\ 3x.(3x^2+5x+2)-4.(3x^2+5x+2)=\\ \\ 9x^3+15x^2+6x-12x^2-20x-8=\\ \\ 9x^3+15x^2-12x^2+6x-20x-8=\\ \\\boxed{ 9x^3+3x^2-14x-8}[/tex]
c ) pode assim também
3x² + 5x + 2
3x - 4
-------------------------
9x³ + 15x² + 6x
-12x² - 20x - 8
-----------------------------------
9x³ + 3x² - 14x - 8